2021
DOI: 10.21037/jtd-20-2790
|View full text |Cite
|
Sign up to set email alerts
|

Changes of quantitative CT-based airway wall dimensions in patients with COVID-19 during early recovery

Abstract: Background: As the coronavirus disease 19 (COVID-19) pandemic evolves, the need for recognizing the structural pulmonary changes of the disease during early convalescence has emerged. Most studies focus on parenchymal destruction of the disease; but little is known about whether the disease affects the airway.This study was conducted to investigate the changes in airway dimensions and explore the associated factors during early convalescence in patients with COVID-19.Methods: We retrospectively analyzed quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Upon comparing patients without COVID-19 with patients in the early recovery period, the researchers reported a greater airway wall thickness in the early recovery period. These results indicated that airway wall thickening in COVID-19 patients did not completely return to normal in the early recovery phase (Xu et al, 2021). In our study, the airways were reconstructed, and lumen measurements were performed.…”
Section: Discussionmentioning
confidence: 75%
“…Upon comparing patients without COVID-19 with patients in the early recovery period, the researchers reported a greater airway wall thickness in the early recovery period. These results indicated that airway wall thickening in COVID-19 patients did not completely return to normal in the early recovery phase (Xu et al, 2021). In our study, the airways were reconstructed, and lumen measurements were performed.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, AWT-Pi10 was not significantly associated with disease severity or other blood biomarkers. One study revealed that patients with COVID-19 have more frequent airway thickening, measured by wall area (%) and AWT-Pi10 compared with those without COVID-19, but there was no significant association between airway thickness and disease severity ( 28 ). The authors suggested that this finding likely results from the fact that the primary structures attacked by SARS-CoV-2 are alveoli, not airways ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the human lung is the most affected organ after SARS-CoV-2 infection [4]. In this context, chest CT has played a key role in the diagnosis and subsequent evaluation of COVID-19 pneumonia [5].…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID-19 pandemic has evolved, there has been a need to recognize and quantify the structural lung changes of this pathology during early convalescence [5]. Most studies and research focus on the damage of the lung parenchyma due to COVID-19 disease and there is not enough information on the impact of the disease on the bronchi and trachea [9], [5]. Furthermore, in some cases evaluation methods using CT can be subjective and have a high dependence on the experience of the evaluator [10].…”
Section: Introductionmentioning
confidence: 99%